Complete genome sequence of Methanocorpusculum labreanum type strain Z. Issue 2 (September 2009) - Anderson, Iain; Sieprawska-Lupa, Magdalena; Goltsman, Eugene; Lapidus, Alla; Copeland, Alex; Glavina Del Rio, Tijana; Tice, Hope; Dalin, Eileen; Barry, Kerrie; Pitluck, Sam; Hauser, Loren; Land, Miriam; et al.
Abstract Methanocorpusculum labreanum is a methanogen belonging to the orderMethanomicrobiales within the archaeal phylumEuryarchaeota . The type strain Z was isolated from surface sediments of Tar Pit Lake in the La Brea Tar Pits in Los Angeles, California.M. labreanum is of phylogenetic interest because at the time the sequencing project began only one genome had previously been sequenced from the orderMethanomicrobiales . We report here the complete genome sequence ofM. labreanum type strain Z and its annotation. This is part of a 2006 Joint Genome Institute Community Sequencing Program project to sequence genomes of diverseArchaea .